Pervasive Aniconism: A Cognitive Approach to Elagabal’s Sacred Stone of Emesa - Hodge, Alex (2024)
Elagabal, the local god of Emesa in Syria, was worshipped in the form of an aniconic stone. Non-figural aniconic cult objects pervade the historical record. Nevertheless, both ancient and modern attitudes toward aniconic cult objects tends to misunderstand and/or denigrate them as primitive or underdeveloped manifestations of divinities. This thesis challenges the traditional view, exploring the phenomenon of aniconic cult objects through the case study of Elagabal’s sacred stone. It uses interdisciplinary cognitive methodologies to argue that the stone was a highly effective and deeply nuanced marker of divine presence. Although aniconic cult objects are frequently unique, it is hoped that this case study yields insight into the cognitive processes and mechanisms underlying human engagement with aniconic cult objects more widely.